Massive sequencing of Ulmus minor’s transcriptome provides new molecular tools for a genus under the constant threat of Dutch elm disease - Perdiguero, Pedro; Venturas, Martin; Cervera, María Teresa; Gil, Luis; Collada, Carmen (Frontiers in Plant Science, 2015)
Elms, especially Ulmus minor and U. americana, are carrying out a hard battle against Dutch elm disease (DED). This vascular wilt disease, caused by Ophiostoma ulmi and O. novo-ulmi, appeared in the twentieth century and killed millions of elms across North America and Europe. Elm breeding and conservation programmes have identified a reduced number of DED tolerant genotypes. In this study, three U. minor genotypes with contrasted levels of tolerance to DED were exposed to several biotic and abiotic stresses in order to (i) obtain a de novo assembled transcriptome of U. minor using 454 pyrosequencing, (ii) perform a functional annotation of the assembled transcriptome, (iii) identify genes potentially involved in the molecular response to environmental stress, and (iv) develop gene-based markers to support breeding programmes. A total of 58,429 putative unigenes were identified after assembly and filtering of the transcriptome. 32,152 of these unigenes showed homology with proteins identified in the genome from the most common plant model species. Well-known family proteins and transcription factors involved in abiotic, biotic or both stresses were identified after functional annotation. A total of 30,693 polymorphisms were identified in 7,125 isotigs, a large number of them corresponding to single nucleotide polymorphisms (SNPs; 27,359). In a subset randomly selected for validation, 87% of the SNPs were confirmed. The material generated may be valuable for future Ulmus gene expression, population genomics and association genetics studies, especially taking into account the scarce molecular information available for this genus and the great impact that DED has on elm populations.